Some physical properties of Australian Nonpareil almonds related to bulk storage - Dingke, Zheng; Fielke, John (International Journal of Agricultural and Biological Engineering, 2014)
The Australian almond industry desires to improve storage of harvested almonds awaiting processing. The present work quantified some storage-related physical properties of almonds. The sample used in the study was Nonpareil almonds with a kernel moisture content of 4.5% d.b. The mass composition of the sample was 55% hull, 32% kernel and 13% shell. Tests showed that the bulk stored in-shell almonds had only 41% of the volume of in-hull almonds and 45% of the mass. Thus removing hulls before storage would result in saving both storage and subsequent transportation costs. Tests simulating various storage heights of almonds showed that a 10 m storage height of almonds increased the bulk density of in-hull almonds from 320 to 355 kg/m3, of in-shell almonds (hull removed) from 356 to 378 kg/m3, and kernels (hull and shell removed) from 604 to 649 kg/m3. A 10 m storage height of almonds reduced the porosity of in-hull almonds from 67% to 64%, of in-shell almonds from 58% to 55%, and of the kernel from 48% to 44%. Observation showed that the change in bulk density and porosity occurred in an exponential manner with fitted curves that provided R2 between 0.97 and 0.99.Keywords: almond, storage, bulk density, true density, porosity, kernel, in-hull, in-shellDOI: 10.3965/j.ijabe.20140705.013Citation: Zheng D. K., Fielke J. M. Some physical properties of Australian Nonpareil almonds related to bulk storage. Int J Agric & Biol Eng, 2014; 7(5): 116－122.